(untitled) (Statistics, Optimization & Information Computing, 2024)
Underlay Device-to-Device (D2D) communications is a promising networking technology intended to boost the spectral efficiency of future cellular networks, including 5G and beyond. When used for distributed caching, where cellular devices store popular files for direct exchange later with other devices away from the cellular infrastructure, the technology bears more fruits such as enhancing throughput, reducing latency and offloading the infrastructure. However, due to their non-orthogonality, underlay D2D communications can result in excessive interference to the cellular user. To avoid this problem, the present article proposes a scheme with two interference-reduction elements: a guard zone intended to allow D2D communications only for devices far enough from the base station (BS), and a pairing strategy intended to allow D2D pairing for only devices that are close enough to each other. We assess the performance of the scheme using a stochastic geometry (SG) model, through which we characterize the coverage probability of the cellular user. This probability is a principal indicator of maintaining the quality of service (QoS) of the cellular user and of enabling successful caching for the D2D user. We introduce in the process a novel empirical technique which, given a desired level of interference, identifies an upper bound for the distance between two devices to be paired without exceeding that level. We finally validate the analytical findings obtained from the model by intensive simulation to ensure the correctness of both the model and the scheme performance. A salient feature of the scheme is that it requires for its implementation no software or hardware modification in the device